Electronic Marketing Practices, Competitive Environment and Performance of Telecommunications Companies in Kenya - Auma Adede, Olgha; Ndungu Kibera, Francis; Odhiambo Owino, Joseph (British Journal of Marketing Studies, 2017)
The objective of the study was to ascertain the effect of e-marketing practices on the performance of telecommunications companies in Kenya. The population of the study was drawn from all telecommunications companies Kenya. Primary and secondary data were used where a semi-structured questionnaire was used to collect primary data while secondary data was extracted from industry performance reports. Data was analyzed using descriptive statistics, factor analysis and regression analysis. The findings showed statistically significant relationship between e-marketing practices and organizational performance. Results of the moderating effect of competitive environment on the relationship were equally statistically significant. The results imply that organizations that have adopted e-marketing practices have also been able to record better performance. This relationship is however moderated by competitive environment meaning that while e-marketing practices contribute to organizational performance, the competitive environments within which they operate require that they develop mechanisms that enable scanning and adapting to competitive environment for competitiveness and better performance. Failure to adapt to the competitive environment can result into organizational demise despite adopting appropriate marketing strategies including, e-marketing practices.